2013
DOI: 10.1186/1472-6963-13-82
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of multiparametric telemonitoring on respiratory outcomes in elderly people with COPD: a randomized controlled trial

Abstract: BackgroundChronic obstructive pulmonary disease (COPD) is a highly prevalent condition associated with a high health care resource consumption and health care expenditures, driven mainly by exacerbations-related hospitalizations. Telemedicine has been proposed as a mean for timely detection of exacerbation, but the available evidence is inadequate to provide conclusive information on its efficacy. The aim of this study is to evaluate the efficacy of a telemonitoring system in reducing COPD-related hospitalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
145
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(154 citation statements)
references
References 28 publications
1
145
0
8
Order By: Relevance
“…Another small RCT (n = 100) from Italy investigated the effects of telemonitoring on respiratory outcomes in an elderly population (65 years of age and older). 129 The intervention group received a wristband with sensors for heart rate, physical activity, near-body temperature, and galvanic skin response. The wristband was also connected to a pulse oximeter.…”
Section: Health Outcomes and Costmentioning
confidence: 99%
“…Another small RCT (n = 100) from Italy investigated the effects of telemonitoring on respiratory outcomes in an elderly population (65 years of age and older). 129 The intervention group received a wristband with sensors for heart rate, physical activity, near-body temperature, and galvanic skin response. The wristband was also connected to a pulse oximeter.…”
Section: Health Outcomes and Costmentioning
confidence: 99%
“…While most previous COPD telemonitoring studies collected data daily, [11] the one study with more frequent collection used a custom wristband that was designed to perform 5 measurements of their oxygen saturation, heart rate, body temperature, and physical activity every 3 hours. [18] However, they obtained on average only 4 recordings per patient day, and data was available for only 60% of patient days, seemingly due to lack of use of their system.…”
Section: Discussionmentioning
confidence: 99%
“…While telemonitoring studies have not consistently reported their recruitment rate [19;20], our recruitment rate was lower than the rate found in the custom COPD wristband study (16% vs 57%) and our dropout rate was higher (43% vs 22%). [18] This may have been due to privacy concerns of recording audio or may have been due to the differences in recruitment settings as one of our sources of patients were from hospitalized patients who were often too sick to participate. We heard from participants that to increase enrolment, we should provide patients with feedback about their activity, their heart rate, and how to better manage their COPD as they did not just want a passive monitoring device.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors used stand-alone spirometers [31,50] with modem transmission three times a week in COPD patients under long-term oxygen therapy (LTOT). PEDONE et al [37] used commercial cellular phones coupled with sensors allowing for five measurements of each parameter over 3 h. MAIOLO et al [42] monitored nocturnal SpO 2 twice a week. Different devices can be hooked-up to the ventilator-monitoring system in order to provide a more comprehensive care.…”
Section: Equipment and Technology For Follow-upmentioning
confidence: 99%